THE ROLE OF KAMPUNG BUDAYA PIJI WETAN IN ADVANCING CULTURE IN THE MURIA REGION : A STUDY OF ARTS CULTURE AND ECONOMY - Nisa, Dea Izatin; Slamet; Widiastuti, Eko H; Nuryanti (Puteri Hijau : Jurnal Pendidikan Sejarah, 2025)
The diminishing awareness among younger generations to preserve local arts and cultural heritage in the era of modernization poses a serious threat to the sustainability of traditional values. Local culture embodies the noble values of a nation and thus must be protected and promoted. This study aims to examine the background of the establishment of Kampung Budaya (Cultural Village) Piji Wetan, the efforts made to promote cultural sustainability, its contribution to the local economy, the challenges it faces in development, and the possible solutions. The research employs a qualitative method with a descriptive approach. Data were collected through observations, in-depth interviews, and documentation, and analysed using Miles and Huberman's model which includes data collection, data reduction, data presentation, and conclusion drawing. The findings reveal that Kampung Budaya Piji Wetan was established as an effort to re-narrate marginalized folklore and respond to the community’s growing awareness of preserving cultural values. Its initiatives are grounded in comprehensive and sustainable community empowerment based on local wisdom, inspired by two key teachings of Sunan Muria—Tapa Ngeli and Pager Mangkuk—which serve as philosophical foundations for cultural identity and community welfare. The village has successfully contributed to the local economy by transforming culture and art into a sustainable economic driver and creating a localized, community-based economic ecosystem. Challenges in development include limited active participation, time constraints among members, and sustaining collective enthusiasm over time. The proposed solutions emphasize strengthening personal engagement, fostering open dialogues to encourage participation, providing emotional support, fair task distribution, and sustaining a sense of collective spirit.